Effects of Preoperative Magnesium Sulphate Infusion on Emergence Agitation and Postoperative Quality of Recovery in Patients Undergoing Thoracoscopic Lobectomy - Pu Y; Geng X; Wang M; Lv G; Hu Z; Fang C; Zhang X; Li W; Fan X; Chen X (Drug Design, Development and Therapy, 2025)
Yutian Pu,1– 3,* Xingyu Geng,1– 3,* Maosan Wang,1– 3 Gaochao Lv,1– 3 Ziwei Hu,1– 3 Can Fang,1– 3 Xinyue Zhang,1– 3 Wanting Li,1– 3 Xiaoxuan Fan,1– 3 Xiuxia Chen1– 3 1Department of Anesthesiology, the Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 2NMPA Key Laboratory for Research and Evaluation of Narcotic and Psychotropic Drugs, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 3Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiuxia Chen, Department of Anesthesiology, the Affiliated Hospital of Xuzhou Medical University, No. 99 huaihai West Road, Xuzhou, Jiangsu, 221002, People’s Republic of China, Tel +86 18052268332, Email cxxlxy@sina.comBackground: Emergence agitation(EA) is common in the early phase of recovery from general anesthesia in adults, which can potentially cause unpredictable harm to both patients and medical staff. This study aimed to examine the effects of preoperative magnesium sulphate infusion on emergence agitation and postoperative quality of recovery in patients undergoing thoracoscopic lobectomy.Patients and Methods: 84 patients undergoing thoracoscopic lobectomy were randomly assigned to either the magnesium sulphate group (group M) or the control group (group C). Group M received a 50 mg/ kg intravenous bolus of magnesium sulphate 20 minutes before induction, whereas group C was administered an equivalent volume of saline. The Riker Sedation-Agitation Scale (SAS) and the 40-item Quality of Recovery questionnaire (QoR-40) were used to evaluate emergence agitation and postoperative quality of recovery, respectively.Results: In comparison to group C, group M demonstrated a significantly lower incidence of EA (9.5% vs 42.9%; OR, 0.14; 95% CI, 0.04– 0.47; P < 0.001) and dangerous agitation (0% vs 14.3%; OR, 2.17; 95% CI, 1.71– 2.75; P =0.011), along with a reduction in the maximal SAS score (P < 0.05). Group M exhibited higher global QoR-40 scores than group C on postoperative day 1 (POD 1)(168.3± 13.8 vs 155.6± 16.5, P< 0.001). Additionally, group M displayed lower Numerical rating scale (NRS) pain scores both at rest and during coughing in PACU and on POD 1 (P < 0.001). There were no significant statistically differences between the two groups in terms of time to extubation, incidence of delayed recovery and residual sedation (P > 0.05).Conclusion: Preoperative magnesium sulphate infusion effectively decreased the incidence and severity of EA in patients undergoing thoracoscopic lobectomy. Furthermore, it alleviated postoperative pain and improved postoperative quality of recovery, without an increase in adverse events.Keywords: magnesium sulphate, preoperative infusion, emergence agitation, recovery quality, thoracoscopic lobectomy